Self-evaluation using the model goal-free evaluation in physics subjects in high schools: abstract - Fitriyanti A. Noho; Masri Kudrat Umar; Ritin Uloli; Abdul Haris Odja; Supartin Supartin; Trisnawaty Junus Buhungo (Jurnal Pijar Mipa, 2023)
The research objective is to evaluate the implementation of a self-evaluation program using an aimless model evaluation of physics subjects in high school. The evaluation focused on how the self-evaluation program was implemented using three stages prepared by the evaluators or researchers in this study, namely the planning stage, the implementation stage, and the final result stage. The research subjects were students of class XI, XII, and a physics teacher. The instrument used was a questionnaire containing statements regarding the implementation of self-evaluations carried out by the teacher. The research method uses a quantitative approach with an evaluative type. Data collection techniques using observation and questionnaires. The results of the research on the implementation of the self-evaluation program in physics subjects in high school obtained an average of 81% and above, this figure is included in the very good criteria, and this shows that the program has been successful, but this needs to be continued to be considered and improved to increase student interest in physics.